2011
DOI: 10.1007/s11252-011-0188-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant species distribution and spatial habitat heterogeneity in the landscape of urbanizing desert ecosystems in Egypt

Abstract: Information on the urban flora and vegetation in the industrial new cities in Egypt are insufficient and far from complete. For this reason, this study was undertaken as the first attempt to fill this gap of knowledge. For two successive years (2004 and 2005), a reconnaissance survey was conducted in four new industrial cities: 6th October, El-Sadat, Burg El-Arab and 10th Ramadan; aiming at: (1) recognizing the floristic composition and vegetation structure of each of the studied cities; (2) identifying the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Our results agree with the previous results, where anthropogenic ecosystem such as roads and urban habitats had high abundance of ruderals and weed species in different ecoregions of Egypt (Shaltout and El-Sheikh, 2003;Abd El-Ghani et al, 2011, 2013, in Europe (Sukopp, 2004;Ziarnek, 2007) and in Australia (Johnston and Johnston, 2004;Stenhouse, 2004). Many of these species differ in their degree of establishment in disturbed habitats (Newsome and Noble, 1986).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with the previous results, where anthropogenic ecosystem such as roads and urban habitats had high abundance of ruderals and weed species in different ecoregions of Egypt (Shaltout and El-Sheikh, 2003;Abd El-Ghani et al, 2011, 2013, in Europe (Sukopp, 2004;Ziarnek, 2007) and in Australia (Johnston and Johnston, 2004;Stenhouse, 2004). Many of these species differ in their degree of establishment in disturbed habitats (Newsome and Noble, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…Four of these species (A. graecorum, B. indica, Salsola kali and Symphyotrichum squamatus) are considered as ruderal communities of urban habitats in Nile Delta (Shaltout and El-Sheikh, 2003). In addition, four species (C. bonariensis, C. acutum, S. glaucus and Heliotropium curassavicum) represented invasive segetal weeds in the Mediterranean arable habitats (Prieur-Richard et al, 2000;Abd El-Ghani et al, 2011). El-Sheikh et al (2012 recognized the dominance of B. indica, C. acutum and S. glaucus during vegetation succession on the constructed landfill along the shore of Lake Burullus.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse habitats are zones of microenvironments at local scales, each habitat supporting a characteristic type of vegetation. As the species distribution is generally limited by its ecological amplitude, [43] climate and habitat filtering, generating species pools, [44], where species adjust their metabolism [45] and produce functional traits as result of adaptation to the microclimates found under variable habitats [46]. Analysis of the present study reveals that highest species concentration was found in gravel rocky terrain, here the life-form composition is dominated by small trees, woody chamaeophytes and therophytes.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the strong environmental filters imposed on USV, the plant communities on vacant land are often diverse, and in some instances, more so than comparable urban or rural habitats [13,18,38,40,45,[75][76][77][78][79]. For example, more tree species were documented on vacant lots in inner-city Cleveland, OH than on residential properties [45].…”
Section: Ecological Considerations Of Usvmentioning
confidence: 99%